Teorização sobre os limites à inserção da saúde bucal na Estratégia Saúde da Família - Elisa Lopes Pinheiro (2021)
This study aimed to theorize by means of social actors’ conception about the reasons for non-inclusion of oral health in the Family Health Strategy in the city of Juiz de Fora, Minas Gerais, Brazil. This is a qualitative, exploratory, descriptive and analytical study that was based on the grounded theory methodology and National Oral Health Policy. Eleven interviews with public managers, delegates who participate in the municipal health council and dental surgeons who belong to public health service were made. The theorization of the study was created through the data analysis process, which resulted as a central category “a consequence of the dominant disease-centred oral health care model". Data were categorized according to a methodological framework. Local social actors’ health concept affected the lack of oral health care teams in the ESF. This theorization identified the origins of the studied phenomenon and can help future local social actors’ political decision making. This study supported the development of the technical product, which aims to share successful experiences, reflections and exchange of knowledge between dentists, oral health managers and all population about the National Oral Health Policy in the state of Minas Gerais through the social media tool podcast.